Towards more sustainable global supply chains? Company compliance with new human rights and environmental due diligence laws - Schilling-Vacaflor, Almut; Gustafsson, Maria Therese (Environmental Politics, 2023)
Binding regulations have, recently, emerged in the Global North with the aim of holding companies accountable for environmental and/or human rights impacts throughout their supply chains. This article develops and applies an analytical framework to analyze corporate accountability dynamics in global trade, with a focus on the French Duty of Vigilance (DV) law. We analyze how companies in the agri-food sector have complied with the law as well as the emergence of new accountability dynamics. We find that while companies have improved their due diligence systems over time, they enjoy much discretion to interpret their obligations according to a managerial logic and to disclose information selectively. Nevertheless, the DV law has contributed to new accountability dynamics, wherein civil society can use civil liability to pressure companies to comply. Overall, the article advances our understanding of company compliance with new supply chain regulations and the accountability dynamics activated by such rules.
CRIS-Team Scopus Importer:2023-11-20
Keywords: business and human rights; due diligence; environmental governance; French Duty of Vigilance law; public policy; supply chains